Dziedzictwo zakonu pijarów w perspektywie badań Zespołu Szkół Pijarskich w Elblągu - Semrau, Katarzyna; Rutkowski , Jarosław (Biuletyn Historii Wychowania, 2020)
The aim of the article is to indicate the heritage of the Piarist order in contemporary education. From the very beginning, activity of Piarist monks was directed at poor children and young people, who through education were to become better citizens and Catholics. Nowadays, this heritage is visible in schools run by Piarist monks. One of the school centers is the Piarist School Complex in Elbląg. An interview with the management and teachers, as well as the results of the survey questionnaire collected, allow you to view the modern heritage of Piarist in this school. The article indicates the Piarist School Complex in Elbląg as an example of contemporary piarist activity, which on the one hand is a modern approach to education, and on the other fulfills the assumptions accompanying from the beginning of the activity of piarist education.